MOVING TOWARDS PHYSICAL AND MENTAL WELL-BEING AFTER BREAST CANCER - Bernardi de Souza, Carolina (2023)
The aim of this study was to understand the effects of physical exercise on the mental health of women recovering from breast cancer. The chosen methodological approach was qualitative. Six women recovering from breast cancer and who performed regular physical exercise participated in the study. The participants shared experiences and perceptions about the effects of physical exercise based on a semi-structured interview. Data were investigated in the light of thematic analysis. The results point out that it is desirable to conciliate the obtaining of pleasure and the therapeutic function of the physical exercise. This can be a means for emotional regulation and can provide exchanges of experiences and affections. This study expanded knowledge in the areas of psycho-oncology and sport psychology.